Investigation of an Entrepreneurial Soul in Boarding Students of Islamic Boarding Schools - Jalal, Novita (Rangkiang: Journal of Islamic Economics and Business, 2024)
The aim of this research is to obtain an overview of the role of Islamic boarding schools in instilling an entrepreneurial spirit in students. This research uses a literature study method using 7 research articles related to cultivating an entrepreneurial spirit in students at Islamic boarding schools. The results of this research show that Islamic boarding schools have a role in building the entrepreneurial spirit of students in Islamic boarding schools through self-confidence, originality (creativity). and innovation) contained in the sermon activities carried out by the students. Results oriented, which can be seen through all activities provided at the Islamic boarding school solely to achieve the Islamic boarding school's vision. Instill mental discipline, namely by providing rules both written and culturally that occur in Islamic boarding schools. Leadership, which is carried out by optimizing the business units owned by the Islamic boarding school, including commerce, animal husbandry, fisheries and agriculture. Islamic Boarding School has a big role in creating modern industrial entrepreneurship, namely creating business units including soap making, convection, cake making, etc., by empowering students and the community through entrepreneurship programs so that they can support and improve the welfare of students and the community by creating lots of jobs.